Dekonstruksi Tokoh Perempuan dalam Novel Madame Bovary: Sebuah Jalan Untuk Melanggengkan Ambisi dan Hasrat: The Deconstruction of Women's Characters in Madame Bovary Novel: a Road to Establish Ambition and Passage - Muhammad Fadli Muslimin (Balai Bahasa Provinsi Papua, 2019)
The study discussed abitu the deconstruction of female character in the novel Madame Bovary using the deconstruction reading method. The purpose of this study was to find binary opposition in the novel and further describe how the author deconstructs female characters in the novel. The method used was descriptive argumentative method. Data was collected in the novel by finding and determining the significance of the quotations which show inconsistencies, contradictions, and logical inaccuracies that can be used to deconstruct and related binary opposition. The data analytical technique was descriptive argumentative in nature which focuses on dismantling the deconstruction narrative in the work. The results showed that there was a binary opposition which opposed each other. The binary opposition that became the center of the main character, Emma, ​​namely wealth, ambition, saturation, sensitivity, and environment became the trigger of instability in identifying her. The author displayed the figure of a woman who rejects the idea that women have no right to have ambitions and satisfy their desires. Emma was present as a person who followed her latent desires and ambitions.